2019
DOI: 10.3389/fpsyg.2019.02190
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics of Emotional Prosody Produced by Prelingually Deaf Children With Cochlear Implants

Abstract: Purpose: Cochlear implants (CIs) provide reasonable levels of speech recognition quietly, but voice pitch perception is severely impaired in CI users. The central question addressed here relates to how access to acoustic input pre-implantation influences vocal emotion production by individuals with CIs. The objective of this study was to compare acoustic characteristics of vocal emotions produced by prelingually deaf school-aged children with cochlear implants (CCIs) who were implanted at the age of 2 and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Wiefferink et al (2013) suggested that reduced auditory exposure and language delays may also lead to delayed social-emotional development and reduced conceptual knowledge about emotions, which in turn result in a negative impact on emotion recognition. This is also evidenced by CI children's reduced differences in mean F0 cues and F0 variations in emotion production compared to their NH peers (Chatterjee et al, 2019). The effects of conceptual knowledge on children's discrimination abilities have also been shown earlier, for instance, in research on pitch discrimination (Costa-Giomi & Descombes, 1996).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Wiefferink et al (2013) suggested that reduced auditory exposure and language delays may also lead to delayed social-emotional development and reduced conceptual knowledge about emotions, which in turn result in a negative impact on emotion recognition. This is also evidenced by CI children's reduced differences in mean F0 cues and F0 variations in emotion production compared to their NH peers (Chatterjee et al, 2019). The effects of conceptual knowledge on children's discrimination abilities have also been shown earlier, for instance, in research on pitch discrimination (Costa-Giomi & Descombes, 1996).…”
Section: Introductionmentioning
confidence: 59%
“…The variability was large and covered the entire performance range, which also demonstrates that the EmoHI test can capture a wide range of performances. Besides age, CI children's performance seems to be heavily affected by differences in social-emotional development causing reduced conceptual knowledge on emotions and their properties (Wiefferink et al, 2013;Chatterjee et al, 2019), and differences in their hearing abilities causing perceptual limitations (Nakata, Trehub & Kanda, 2012). For instance, individual differences in CI children's vocal emotion recognition abilities may also rely on their F0 discrimination thresholds, which are generally higher and more variable in CI children compared to NH children (Deroche et al, 2014).…”
Section: Childrenmentioning
confidence: 99%
“…In recent years, many individuals with hearing impairments receive cochlear implants (CI). CIs provide little pitch information but do provide other cues, such as duration and intensity (Chatterjee et al, 2019). CI users typically experience difficulties in perceiving emotional prosody (e.g., Chatterjee et al, 2015;Hopyan-Misakyan et al, 2009;Paquette et al, 2018), and identifying producers' sex or identity (e.g., Fu et al, 2005;Fuller et al, 2014;Mühler et al, 2009).…”
Section: Vocal Production and Hearing Disordersmentioning
confidence: 99%
“…Several suprasegmental deficits are characteristic of the speech of the hearing-impaired particularly prosodic control of intonation and stress [12,13]. Regarding affective prosody production, some studies showed that CI children produce emotions with a limited range of f0 and intensity with little contrasts between different emotions in addition to an imprecise imitation of emotions due to inappropriate pitch inflection and an overall monotonous speech [14,15].…”
Section: Introductionmentioning
confidence: 99%